A randomized controlled trial comparing the GLP‐1 receptor agonist liraglutide to a sulphonylurea as add on to metformin in patients with established type 2 diabetes during Ramadan: the Treat 4 Ramadan Trial. Issue 6 (26th January 2014) - Brady, E. M.; Davies, M. J.; Gray, L. J.; Saeed, M. A.; Smith, D.; Hanif, W.; Khunti, K.
<x xml:space="preserve">Abstract</x> Aims To compare a sulphonylurea with the glucagon like peptide‐1 (GLP‐1) receptor agonist liraglutide in combination with metformin in patients on mono/dual oral therapy with established type 2 diabetes fasting during Ramadan. Methods Ninety‐nine adults intending to fast during Ramadan [50% male, mean age 52 years, body mass index (BMI) 32 kg/m2] were randomized from two UK sites. Baseline data were collected ≥14 days prior to Ramadan and at 3 and 12 weeks after Ramadan. Results At 12 weeks, more patients in the liraglutide compared with the sulphonylurea group achieved a composite endpoint of haemoglobin A1c (HbA1c) < 7%, no weight gain and no severe hypoglycaemia but this did not reach statistical significance [odds ratio (OR) 4.08, 95% confidence interval (CI) 0.97, 17.22, p = 0.06]. From a baseline of 7.7% there was no change in HbA1c at 12 weeks in the sulphonylurea (+0.02%) compared with a 0.3% reduction in the liraglutide group (adjusted coefficient −0.41, 95% CI −0.83, 0.01, p = 0.05). Significant reductions were also observed in weight and diastolic blood pressure (BP) in the liraglutide compared with the sulphonylurea group. Treatment satisfaction was comparable across the treatment groups. There were no episodes of severe hypoglycaemia in either group, however, self‐recorded episodes of blood glucose ≤3.9 mmol/l were significantly lower with liraglutide (incidence rate ratio 0.29, 95% CI 0.19, 0.41, p < 0.0001). Conclusions Liraglutide compared with sulphonylurea is well tolerated and maybe an effective therapy in combination with metformin during Ramadan with more patients able to achieve target HbA1c, lose or maintain weight with no severe hypoglycaemia. This was achieved with a high level of treatment satisfaction.